Bio-control of rice sheath blight through antagonists in field - JANKI KANDHARI*, M. TAMILVANAN and (Indian Phytopathology, 2009)
The present study was undertaken to assess the per cent disease incidence, relative lesion height, disease severity, 1000 grain weight, grain yield and straw yield against sheath blight (Rhizoctonia solani) of rice through two different antagonists, individually as well as in combination. One set of plants was sprayed one day before inoculation (pre-inoculation) and the other set one day after inoculation (postinoculation). For comparison, one set of plants was also sprayed with sheathmar 3L (2.5%) and Kalisena (A. niger AN-27 @ 106 cfu ml-1). Pre-inoculation spray of Trichoderma koningii 5201 + Chaetomium cochliodes 3319 showed maximum reduction (55.1%) of the disease incidence, disease severity (70.8 %), relative lesion height (48.1%). Maximum 1000-grain weight, grain yield and straw yield of 12.3g, 3.1kg and 13.5kg respectively was obtained from pre-inoculation spray of T. koningii 5201 + C. cochliodes 3319.